CONTRIBUTION OF RAIN-FEED RICE FARMING TO HOUSEHOLD INCOME IN RANTO DISTRICT PEUREULAK, EAST ACEH DISTRICT - Suhartini; Jamilah; Setia Budi (Universitas Efarina, 2022)
The study was conducted in Ranto Peureulak District, East Aceh Regency from October-November 2021. This study aims to of this study was to analyze the income of rainfed lowland rice farmers and analyze the contribution of rainfed lowland rice farming to household income in Ranto Peureulak District, East Aceh Regency. the object of research is carried out intentionally (purposively). The types of data used are primary data and secondary data. The type of data used consists of descriptive qualitative and descriptive quantitative approaches. The results of this study indicate that the average income of rainfed lowland rice farming in Ranto Peureulak District, East Aceh Regency for per self-owned land area is IDR 2,724,930.7.00 for per arable land area of ​​IDR 1,871,354.6, 00 and per area of ​​leased land. amounting to IDR 217,000.2.00 per hectare. Rainfed lowland rice farming contributes to the household income of farmers with own land status by 34.5%, for smallholders by 40.1% and for tenant farmers by 6.7%.